2014
DOI: 10.1016/j.jviromet.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of Cyprinid herpesvirus-3 replication by RNAi

Abstract: Cyprinid herpesvirus-3 (CyHV-3) is an etiological agent of a notifiable disease that causes high mortality rates affecting both the common and koi carp Cyprinus carpio L. There is no current treatment strategy to save CyHV-3 infected fish. RNA mediated interference (RNAi) is an emerging strategy used for understanding gene function and is a promising method in developing novel therapeutics and antiviral medications. For this study, the possibility of activating the RNAi pathway by the use of small interfering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
15
2
Order By: Relevance
“…1B) confirmed that the treatment of cells with single target siRNA did not lower CPE formation (survival of 48% to 57% of cells), when compared to non-treated and nonsense siRNA treated cells (both destruction of 50% of cells). In contrast to our observations, another recent study showed that treatment of CyHV-3 infected CCB cells with siRNA targeting against a single gene, CyHV-3 DNA polymerase, could also be effective in inhibiting virus replication (Gotesman et al 2014). However, as Gotesman et al (2014) analysed the number of released virus particles and not the influence on cell viability, the results are difficult to compare with the observations presented here.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…1B) confirmed that the treatment of cells with single target siRNA did not lower CPE formation (survival of 48% to 57% of cells), when compared to non-treated and nonsense siRNA treated cells (both destruction of 50% of cells). In contrast to our observations, another recent study showed that treatment of CyHV-3 infected CCB cells with siRNA targeting against a single gene, CyHV-3 DNA polymerase, could also be effective in inhibiting virus replication (Gotesman et al 2014). However, as Gotesman et al (2014) analysed the number of released virus particles and not the influence on cell viability, the results are difficult to compare with the observations presented here.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our observations, another recent study showed that treatment of CyHV-3 infected CCB cells with siRNA targeting against a single gene, CyHV-3 DNA polymerase, could also be effective in inhibiting virus replication (Gotesman et al 2014). However, as Gotesman et al (2014) analysed the number of released virus particles and not the influence on cell viability, the results are difficult to compare with the observations presented here. Interestingly, when the virus was treated with a mixture of all four oligos, a statistically significant reduction in the number of killed cells was achieved (survival of 79% of cells).…”
Section: Resultscontrasting
confidence: 99%
“…Similar to mammalian herpesviruses, gene transcripts known to be involved in DNA replication were expressed early, while proteases and enzymes involved in virion assembly and maturation were expressed late (Ilouze et al, 2012a;van Beurden et al, 2013). Inhibition of some E genes involved in DNA replication (e.g., TK and DNA polymerase) by specific siRNA decreased viral release from infected cells (Gotesman, Soliman, Besch, & El-Matbouli, 2014).…”
Section: Transcriptomementioning
confidence: 97%
“…Although there have been several approaches proposed to diminish the consequences of CyHV-3 infection, the problem has not been solved. The costs as well as the advantages and disadvantages of individual approaches have to be considered (1,4,11,23). Oral administration of the anti-CyHV-3 remedy would be the most convenient treatment that could be applied against CyHV-3.…”
Section: Introductionmentioning
confidence: 99%